PEMBELAJARAN MEMBACA AL-QUR'AN BERBASIS PESANTREN DAN IMPLIKASINYA TERHADAP PENGEMBANGAN MATERI AJAR PAI - Tamara Lengkap, - (2022)
The existence of learning the Quran has a purpose to make students correctly place the sound of the letter according to the makhraj, harakat and the place where it stops. However, in learning the Quran, there are still many gaps, causing several problems, namely the ability to read the Quran in Indonesia is still low, there are still many Muslims who do not understand the basic tajweed. This study specifically aims to: (1) describe the lesson plan for the book of Tuhfatul Al-Aṭfāl (2) describe the learning process of the book of Tuhfatul Al-Aṭfāl (3) describe the achievement of students' reading abilities in the Quran after following the learning of the book of Tuhfatul Al-Aṭfāl (4) describe the implications of learning the book of Tuhfatul Al-Aṭfāl in Islamic Boarding School on the development of PAI teaching materials. This study uses a qualitative approach with a descriptive method. Researchers become a key instrumen in research. They are collecting data using the techniques of observation, interviews, and documentation. From this study, it was found that learning to read the Koran based on pesantren, namely by using the Tuhfatul Al-Aṭfāl book, is very suitable for beginners who want to learn basic tajwid and the implication for the development of PAI teaching materials from learning the book of Tuhfatul Al-Aṭfāl at the Islamic Boarding School is the addition of recitation material on lam fi'il and the classification of how to read the laws of idgham mitslain, mutajanisain and mutaqaribain.